Anthropic Action and the Eutrophization Process in the Paraíba do Meio River - Santos, Everson Oliveira; Medeiros, Paulo Ricardo Petter (Sociedade & Natureza, 2023)
The appropriation and use of a hydrographic basin by society is a historical process, necessary and, above all, a generator of environmental problems that greatly alter the quality of water. One of the problems related to water quality is eutrophication. Many aquatic ecosystems have suffered from this problem, which consists of large inputs of Phosphorus and Nitrogen introduced into the riverbed, for example, through domestic and/or industrial effluents. This context of change in water quality by human action triggers the significant growth of phytoplanktonic and phytobenthic organisms, thus causing an imbalance in the dynamics of the aquatic ecosystem, as well as damage to society. In this context, this study aimed to evaluate the Trophic State of the Paraíba do Meio River and understand the unfolding and influences of society's relationship with the river and how this relationship has contributed to the eutrophication process. The materials and methods were based on: data acquisition of chemical and physical parameters from campaigns carried out monthly during the hydrological year of 2013; flow and precipitation data; adequate sanitary sewage data; laboratory analyses; determination of the Trophic State Index by the TRIX Model. It was evidenced that due to the varied anthropic activities that occurred in the hydrographic basin in question, with the significant introduction of nutrients such as Phosphorus and Nitrogen in the river bed, during the hydrological year of 2013, the Paraíba do Meio river presented different stages of eutrophication that range from mesotrophic to eutrophic.